Periphery Israel's search for Middle East allies - Alpher, Joseph (Rowman & Littlefield, 2015)
The book analyzes Israel's strategic thinking about the Middle East region, evaluating its success or failure in maintaining both Israel's security and the viability of Israeli-American strategic cooperation.